Implantación y Calibración del Presiómetro Ménard para estimación de capacidad de soporte y deformabilidad de suelos en cimentaciones de proyectos ICE. - Jiménez-Duarte, Pricilla (Instituto Tecnológico de Costa Rica, 2007)
The pressuremeter test is used in situ soil testing. The test consist of placing a cylindrical probe in a borehole with a diameter that allows the probe to be in contact with the soil. The active part of the pressuremeter is the probe because expands the soil cavity and measures deformations. This expansion is done by injecting air and water to the cells of the probe. The gas and water are injected by the control unit, which is a box containing several valves and gauge. The other part of the pressuremeter is the coaxial tube, this is a connector between the probe and the control unit. The purpose of this work is to conduct a literary review on different methodologies to obtain parameters from the PMT, and it`s application in geotechnical engeneering investigations. Results obtained from a serious of test performed, as well as from historical date available at ICE suggest that the most important variable at test is the limit pressure and pressiometric modulus. However pressure limit is difficult to obtain from the test it has to be calculated by extrapoling the results. Once the pressure limit and the modulus are obtained it is possible to calculate the undrained shear strength, bearing capacity and settlements by correlations.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007
Keywords: Presión Límite; Resistencia Límite; Asentamiento; PMT